(untitled) (LACCEI, 2024)
The pollution of rivers has generated great concern on the part of governments and the population, due to the acceleration of urbanization and the rapid development of the economy. The objective of this research is to analyze the pollutant load from the city of Santiago de los Caballeros (Dominican Republic) to the Yaque del Norte river. This city is the second largest in the Dominican Republic by number of inhabitants, and the Yaque del Norte River is the longest river in the country. A total of 288 surface water samples were collected corresponding to two monitoring sites in the Yaque del Norte river, one at the entrance of the city and another at the exit. The samples were collected, monthly, from January 2010 to December 2021. The results show that the city of Santiago de los Caballeros increases the degree of contamination of the Yaque del Norte River, increasing the contamination in the parameters of dissolved oxygen, turbidity, color, conductivity, total dissolved solids, hardness, alkalinity, suspended solids, chemical oxygen demand, biochemical oxygen demand, nitrates, nitrites, ammonium, total nitrogen, total phosphorus, rotophosphates, chlorides, fecal coliforms, and total coliforms. It is determined that it is necessary to adopt an economic and feasible method to carry out an analysis of the causes of surface water pollution, to help formulate water pollution control policies in a timely manner in response to the rapid urban expansion of the city.